2016
DOI: 10.1097/j.pain.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Striatal-enriched protein tyrosine phosphatase modulates nociception

Abstract: The information from nociceptors is processed in the dorsal horn of the spinal cord by complex circuits involving excitatory and inhibitory interneurons. It is well documented that GluN2B and ERK1/2 phosphorylation contributes to central sensitization. Striatal-enriched protein tyrosine phosphatase (STEP) dephosphorylates GluN2B and ERK1/2, promoting internalization of GluN2B and inactivation of ERK1/2. The activity of STEP was modulated by genetic (STEP knockout mice) and pharmacological (recently synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…3B). From the totality of our past (Xu et al , 2015 a ; Azkona et al , 2016; Hildebrand et al , 2016; Saavedra et al , 2016) and present evidence, we conclude that loss of STEP 61 links BDNF/KCC2-dependent disinhibition to the potentiation of GluN2B NMDARs at lamina I synapses in a pathological spinal mechanism that is conserved between chronic inflammatory and neuropathic pain states.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…3B). From the totality of our past (Xu et al , 2015 a ; Azkona et al , 2016; Hildebrand et al , 2016; Saavedra et al , 2016) and present evidence, we conclude that loss of STEP 61 links BDNF/KCC2-dependent disinhibition to the potentiation of GluN2B NMDARs at lamina I synapses in a pathological spinal mechanism that is conserved between chronic inflammatory and neuropathic pain states.…”
Section: Resultsmentioning
confidence: 64%
“…Because disinhibition can trigger STEP 61 downregulation and STEP 61 regulates Fyn and GluN2B signalling in dorsal horn neurons (Li et al , 2015; Xu et al , 2015 a , 2018; Azkona et al , 2016), we asked whether loss of STEP 61 directly couples KCC2-dependent disinhibition to the potentiation of GluN2B NMDARs by Fyn in the ex vivo BDNF model of pathological pain. To investigate this, we explored the effects of STEP 61 antagonists and agonists on superficial dorsal horn synaptosomes from saline- versus BDNF-treated rodent spinal cords.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of glutamate receptor subunits, it dephosphorylates the GluN2B subunit of NMDARs at Tyr1472, counteracting the activity of src kinases, and promotes the internalization from surface membranes of the NMDARs, thus contributing to the homeostatic stabilization of the excitatory synapses [ 44 46 ]. In the spinal cord, the role for STEP61 in the modulation of nociception and in the development of inflammatory pain has been demonstrated [ 47 , 48 ]. Li and collaborators [ 48 ] demonstrated that the hyperphosphorylation of GluN2B, fyn, and ERK2, induced by a reduction in the activity of STEP61, was critical to trigger pain hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of STEP61 increases active Fyn and phosphorylation of GluN2B [79,80]. Inflammation-induced hyperalgesia leads to decrease in STEP61 activity (by both phosphorylation at serine 221 residue and cleavage) with concurrent increases in phosphorylated GluN2B in the spinal cord [82,83]. In 2019, we showed that STEP61 is significantly reduced at the superficial dorsal horn in a persistent inflammatory pain model and an ex vivo BDNF model of pathological pain processing [84].…”
Section: Step61 -The Linker Between Disinhibition and Increased Excitmentioning
confidence: 72%
“…Our finding suggests that this pathway may be conserved in these pain conditions in human males as well, although further experiments such as biochemical analysis on spine donor samples from chronic pain patients and assays to assess whether BDNF levels are elevated in patients with chronic pain must be performed for confirmation. Further, given the important role of STEP61 as the linker between disinhibition and GluN2B-mediated excitation, and its modulatory effects on all the critical elements -TrkB, Fyn and GluN2B -of the BDNF pain pathway [79,80,82,84,100] our observation that STEP61 is also downregulated at the superficial dorsal horn synapses by BDNF in human males similar to male rodents may prompt future pain research to investigate whether modulating active STEP61 levels can change pain hypersensitivity in rodents and if those findings are relevant to humans. This may be a promising avenue as directly manipulating NMDARs and BDNF-TrkB signalling can lead to various pathologies [66,[101][102][103].…”
Section: Discussionmentioning
confidence: 99%